In-silico Analysis of Bioactive Compounds from Staghorn Fern (Platycerium bifurcatum C. Chr.) as Anti-Inflammatory Drug Candidates for Inhibiting Cyclooxygenase-2 Enzyme - Alfitriyah, Miftakhul Rahmadai; Rohman, Fatchur; Setiowati, Frida Kunti (LenteraBio : Berkala Ilmiah Biologi, 2025)
Inflammation can be suppressed through anti-inflammatory mechanisms by inhibiting the performance of the cyclooxygenase-2 enzyme, which results in decreased prostaglandin synthesis so that clinical signs of inflammation can be reduced. Anti-inflammatory mechanisms can be carried out by groups of NSAID drugs such as acemetacin, but continuous use can cause side effects, thus opening the way for the use of natural ingredients as alternative treatments such as P. bifurcatum C. Chr leaves. This study aims to analyze the potential of bioactive compounds in P. bifurcatum C. Chr leaves as anti-inflammatories based on their binding affinity values ​​with the cyclooxygenase-2, biooral potential, ADMET, and toxicity tests through an in silico approach with molecular docking techniques. The results showed that in P. bifurcatum C. Chr leaves, gallic acid and quercetin compounds are present. The binding affinity value control acemetacin (control) is -7,9 kcal/mol, gallic acid is -6.3 kcal/mol, and quercetin is -8.8 kcal/mol. The acemetacin (control), gallic acid, and quercetin bind to the identical six amino acid residues of the cyclooxygenase-2, namely THR A:212, TYR A:385, HIS A:388, TRP A:387, ALA A:199, LEU A:390. Quercetin and gallic acid can be absorbed, distributed, metabolized, and excreted and do not show any health risk. They can be consumed orally safely and do not cause cancer in the long term, so that they can be candidates for anti-inflammatory drugs.